2023
DOI: 10.1038/s41541-023-00620-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with matrix-, nucleoprotein and neuraminidase protects against H3N2 influenza challenge in pH1N1 pre-exposed pigs

Abstract: There is an urgent need for influenza vaccines providing broader protection that may decrease the need for annual immunization of the human population. We investigated the efficacy of heterologous prime boost immunization with chimpanzee adenovirus (ChAdOx2) and modified vaccinia Ankara (MVA) vectored vaccines, expressing conserved influenza virus nucleoprotein (NP), matrix protein 1 (M1) and neuraminidase (NA) in H1N1pdm09 pre-exposed pigs. We compared the efficacy of intra-nasal, aerosol and intra-muscular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Additionally, pigs exhibit a comparable distribution of sialic acid receptors in the respiratory tract (38). We have established a robust influenza challenge pig model to study immunity to influenza and evaluate the efficacy of novel vaccines and therapeutics (39)(40)(41)(42). We have further shown that pig immune responses following infection with H1N1pdm09 influenza virus are similar to those induced in humans (43).…”
Section: Introductionmentioning
confidence: 94%
“…Additionally, pigs exhibit a comparable distribution of sialic acid receptors in the respiratory tract (38). We have established a robust influenza challenge pig model to study immunity to influenza and evaluate the efficacy of novel vaccines and therapeutics (39)(40)(41)(42). We have further shown that pig immune responses following infection with H1N1pdm09 influenza virus are similar to those induced in humans (43).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, local IgA and IgG can be detected as early as 4-5 days after IAV-S infection ( Lee et al., 1995 ; Larsen et al., 2000 ). Recent research correlated local and systemic antibodies elicited after different routes of immunization in pigs and observed that either local or systemic neutralizing antibody responses can provide protection against IAV-S infection ( Vatzia et al., 2023 ). Cross-protective antibody responses against genetically divergent HA proteins are dictated by the overall genetic similarly of the HA protein and how well the targeted epitopes match ( Reeth et al., 2004 ; Kreijtz et al., 2011 ).…”
Section: Current Challenges In Developing a Universal Iav-s Vaccinementioning
confidence: 99%
“…injection evoked systemic antibody responses, while aerosol immunization led to mucosal formation of specific T cells and IgGs. Notably, shedding of the H3N2 virus challenge and lung damage were reduced in both cases [ 68 ].…”
Section: Development Of Np-based Broadly Protective Vaccine Prototypesmentioning
confidence: 99%